Multi-core vesicle nanoparticles for controlled delivery of protein drug - Yuk, Soon Hong; Oh, Keun Sang; Kim, Seung Ki; Lee, Jin Ho; Cho, Sun Hang; Kim, Kwangmeyung; Jeon, Hyesung; Kwon, Ick Chan (POLYMER SOC KOREA, 2012)
The Pluronic/poly(ethylene glycol) composite nanoparticles (NPs) composed of Pluronic F-68, liquid poly(ethylene glycol) (PEG; molecular weight, 400) and human growth hormone (hGH) were stabilized with the vesicle fusion. When hGH-loaded Pluronic/PEG composite NPs were mixed with vesicles in the aqueous medium, hGH-loaded Pluronic/PEG composite NPs were incorporated into vesicles to form multi-core vesicle NPs. The morphology and size distribution of multi-core vesicle NPs were observed using field emission scanning electron microscopy, cryo-transmission electron microscopy, and a particle size analyzer. When multi-core vesicle NPs were applied as a delivery system for the protein drug, a sustained release pattern of hGH was observed.
Keywords: GH-DEFICIENT PATIENTS; GROWTH-HORMONE GH; COPOLYMER; FUSION; ENCAPSULATION; MICROSPHERES; SPECTROSCOPY; STABILITY; BILAYER; SYSTEMS